Bio nano ink for 4D printing membrane proteins. Issue 66 (25th August 2017) - Mathews, Anu Stella; Abraham, Sinoj; Kumaran, Surjith Kumar; Fan, Jiaxin; Montemagno, Carlo
Abstract : Photo curable bio-nano ink was designed, developed and printed using a stereolithographic printer. Abstract : The transfer of bio-functionality from natural living organisms to stable engineered environments opens a wide horizon of applications. Our work focusses on the creation of materials and devices that transform bio traits and collect, process and act on the information in response to changes in their local environment, thus promoting additive manufacturing from 3D space to a four-dimensional, functional space. In this work we have expanded the set of tools enabling the incorporation of biological function as an intrinsic property in the devices we print with a new class of light curable bio nano ink. This novel approach allows the 3D printing of acrylic polymer compositions containing biological materials, especially, membrane proteins using a photo (407 nm) curing stereolithography (SLA)/digital light processing (DLP) 3D printer. Retaining the bio functionality of these proteins gives a fourth dimensional (4D) aspect to this construct. Herein, we report the 4D printing of a bio-inspired nano hybrid electrode for water-splitting applications using a polymeric resin with proton-pumping bacteriorhodopsin (bR), silver nanoparticles (Ag NP) and carbon nanotubes (CNT). These printed photo electrochemical cells exhibit high durability, low onset over potential, and upon light irradiation (535 nm) produces hydrogen by a synergistic effect of Ag NP and bR.